2022
DOI: 10.21787/jbp.14.2022.251-262
|View full text |Cite
|
Sign up to set email alerts
|

Development of Micro, Small, and Medium Enterprises Through Geoproducts for Geopark Gorontalo

Abstract: Geopark is an area that combines the uniqueness of geology, biodiversity, and cultural diversity that is managed for the needs of conservation, education, and sustainable economic development of the community. The existence of this Geopark has opened up opportunities and become a great chance for local communities. Gorontalo province has the biggest potential natural resources for development; in this matter, we need local creativity to build efforts in special characters and also unique for itself. The Goront… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…Apart from that, on average, LKM-A is only able to lend its members a maximum of IDR3,000,000 a year or IDR1,000,000 per planting season, which is not yet able to improve farming for the better. This is in accordance with research by Butolo (2022) and Zugravu-Soilita et al (2021) that one of the problems of small businesses is capital resources. Thus, it can be concluded that hypothesis number 6, that private land ownership status can reduce the risk of poverty, is rejected.…”
Section: Resultssupporting
confidence: 92%
“…Apart from that, on average, LKM-A is only able to lend its members a maximum of IDR3,000,000 a year or IDR1,000,000 per planting season, which is not yet able to improve farming for the better. This is in accordance with research by Butolo (2022) and Zugravu-Soilita et al (2021) that one of the problems of small businesses is capital resources. Thus, it can be concluded that hypothesis number 6, that private land ownership status can reduce the risk of poverty, is rejected.…”
Section: Resultssupporting
confidence: 92%
“…Strategi bagi UMKM memiliki peranan sebagai faktor utama dalam proses pencapaian pengembangan kegiatan UMKM serta pemberdayaan masyarakat, dan juga sebagai suatu cara upaya untuk penciptaan inovasi UMKM. Perencanaan strategis merupakan landasan utama bagi para pelaku UMKM untuk bergerak dalam mengembangkan usahanya, sehingga dapat dikatakan bahwa strategi merupakan suatu konsep dalam usaha untuk mendesain pengembangan usaha yang mana diupayakan agar UMKM dapat naik tingkat [9]. Terdapat beberapa elemen strategi dalam meningkatkan kinerja UMKM diantaranya: 1) resources and capabilities or Process Technic Capasity mengacu kepada startegi dalam pengeloaan sumber daya dan juga kemampuan yang diarahkan untuk membantu pelaksanaan serta pengambilan keputusan, 2) Market Regulation and SME Regulation mengacu kepada kepada proses penentuan kebijakan-kebijakan pemerintah ataupun Usaha Mikro, kecil dan menengah dalam upaya peningkatan pengembangan UMKM tersebut, 3) Employee skill merupakan salah satu bentuk strategi yang dikembangkan untuk pemahamanan kemampuan, keterampilan serta pengetahuan pelaku UMKM dalam mengidentifikasikan dan menganalisis Kekuatan, kelemahan, peluang dan ancaman bagi UMKM.…”
Section: Penulis Pertama Dkkunclassified
“…Socioeconomic conditions and resources are the system context that forms the background for collaboration between institutions. Meanwhile, Leadership, Dependency, and Uncertainty are factors that drive Collaborative Governance (Butolo, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This provides economic value and strengthens local cultural identity and sustainability. Besides that, Regional Governments have many opportunities and challenges when they are given autonomy in financial management and innovation in potential financial sectors (Butolo, 2022).…”
Section: Introductionmentioning
confidence: 99%